Studies on Neotropical Cerrenaceae (Basidiomycota, Polyporales): a new species of Irpiciporus from Brazil - Regio, Nicolas Do Carmo; Westphalen, Mauro C.; Silveira, Rosa Mara Borges Da (Phytotaxa, 2024)
In this study, Irpiciporus prismaticus sp. nov. is proposed based on morphological and phylogenetic analyses. Specimens were collected in the Atlantic Forest areas of southern Brazil and nuclear ribosomal DNA ITS and LSU regions were sequenced. This is the first time that Brazilian specimens of Irpiciporus have been sequenced and phylogenetically analyzed. Irpiciporus prismaticus is characterized by pileate to effused-reflexed basidiomes with a hydnoid to irpicoid hymenophore and a context distinctly duplex in pileate specimens. Microscopically, it resembles other species of the genera, but differs in the presence of prismatic crystals throughout the context and teeth trama, and smaller basidia. Phylogenetically, it is closely related to the African species, I. branchiformis, and the Asian species, I. sinuosus. Furthermore, I. rajchenbergii, a resupinate species described from adjacent regions in Brazil, is confirmed as a different taxon in the genus based on morphological comparisons of herbarium collections. Additionally, specimens of Cerrena multipileata from areas near the type locality were sampled and sequenced and an updated morphological description is provided. An updated key for Irpiciporus, including our newly described species, and brief discussions about the genera treated here are also provided.